Emperical Characterization of Oil Shale Cratering Experiments - K Lombardo (International Society of Explosives Engineers, 1983)
Numerous small- and intermediate-size cratering experiments have been conducted in Piceance Creek Basin oil shale at the Colony and Anvil Points oil shale mines near Rifle, Colorado. The purpose of these experiments was to evaluate scaling as a tool to infer the behavior of large-scale tests from small-scale experiments, to calibrate the hydrodynamic computer codes used to model explosive fragmentation of oil shale, and to investigate the influence of bedding plane orientation, natural joints, fractures, and the grade of oil shale on rock fragmentation.